Rethinking Rationality: Current Criticism of the Hard Core of Mainstream Economics - Diab, Mohamed (Finance and Business Economies Review, 2022)
The rationality postulate is the hard-core - according to Imre Lakatos' concept - for the research program of mainstream economics. Economists have surrounded rationality with a thick protective belt of auxiliary hypotheses to receive criticism on behalf of it. However, the defense on rationality did not last long. Economic rationality has been exposed to criticism noticeably in the last decades. This article offers a critical report on economic rationality from dissident schools such as the Keynesian school or Islamic criticism, which presents another meaning of rationality, based on moral and complex goals, not only on material utility